1996
DOI: 10.1021/ja952928a
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Bonded Fluorine as a σ-Donor for Groups I and II Metal Ions in Partially Fluorinated Macrocycles

Abstract: Novel fluoro cryptands and fluoro crown ethers were synthesized in good yields in the reactions of 1,3bis(bromomethyl)-2-fluorobenzene with diaza-18-crown-6 [the resulting two macrocycles are abbreviated as FN 2 O 4 (1 + 1 product) and (FN 2 O 4 ) 2 (2 + 2 product)], diaza-15-crown-5 [product abbreviated as FN 2 O 3 ], aza-(3n)-crown-(n) (n ) 4, 5, 6) [F(NO 3 ) 2 , F(NO 4 ) 2 , F(NO 5 ) 2 ], and the potassium salts of tetraethyleneglycol [FO 5 ] or pentaethylene glycol [FO 6 ] and in the reaction of 1-(bromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 73 publications
4
55
0
Order By: Relevance
“…The fluorine-free cryptands HN 2 O 3 and HN 2 O 4 were synthesized according to the literature procedure. [7] The heptafluorobutyrates of the alkaline earth cations were prepared by the addition of solid alkaline earth metal hydroxides to a concentrated aqueous solution of heptafluorobutyric acid (Aldrich) until no more dissolution of the hydroxide could be observed. The reaction mixture was filtered, and the volatile substances evaporated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluorine-free cryptands HN 2 O 3 and HN 2 O 4 were synthesized according to the literature procedure. [7] The heptafluorobutyrates of the alkaline earth cations were prepared by the addition of solid alkaline earth metal hydroxides to a concentrated aqueous solution of heptafluorobutyric acid (Aldrich) until no more dissolution of the hydroxide could be observed. The reaction mixture was filtered, and the volatile substances evaporated.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Apart from X-ray crystal structure determinations, NMR spectroscopy and picrate extraction were used to investigate the nature of CF ± metal ion interactions. [7] Erker et al, [8] Marks et al, [9] and others [10] discovered that the CF groups of fluorinated phenylborate ligands can allow hemilabile coordination of cationic zirconocenes. Erker et al suggested that such weak contacts might be used to reversibly control the catalysis of Ziegler ± Natta-type olefin transformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plenio and Diodone have also reported fluorocrown ethers (Table 5), which exhibit chemical shift response upon binding Ca 2þ [314]. Of course, calcium could potentially be analyzed directly by 43 Ca NMR, however, its natural abundance is <0.2%, its sensitivity is <1% that of 1 H, and being quadrupolar, it is liable to extensive line broadening [59].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…These investigators have tumor oxygenation as part of therapeutic planning. Patients also reported a series of fluorocyclophanes and fluoro crown could be stratified according to baseline hypoxia to receive ethers to explore specific cation binding (e.g., K+, Li+, Na+, adjuvant interventions designed to modulate P 0 2, or more Ba 2 +, Sr 2 +, Ca 2 +, and associated chemical shifts [136,148]. intense therapy as facilitated by IMRT (Intensity Modulated Radiation Therapy).…”
Section: Other Biological Relevant Ligandsmentioning
confidence: 99%